2018
DOI: 10.1016/j.joule.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Quinone-Mediated Electrochemical O2 Reduction Accessing High Power Density with an Off-Electrode Co-N/C Catalyst

Abstract: Dissolved organic redox mediators enable transport of electrons and protons between an electrode and off-electrode heterogeneous catalysts. A new tetrasubstituted quinone has been developed that exhibits excellent solubility and stability under strongly acidic conditions and supports electrochemical reduction of O 2 in an off-electrode packed-bed reactor containing a heterogeneous Co-N/C catalyst. These components are integrated in a ''flow-cathode'' fuel cell system that achieves high current and power densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…[ 14,23,24 ] Hydroquinones 6 and 7 were synthesized by addition of sodium mercaptoethanesulfonate to benzoquinone. The tris‐thioether compound 6 is an analogue of the major byproduct formed during the previously reported synthesis of 4 , [ 22 ] and it was produced by attempting the synthesis of 5 at elevated temperature (see Supporting Information). The yield of the byproduct was instead improved, allowing 6 to be isolated for further studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 14,23,24 ] Hydroquinones 6 and 7 were synthesized by addition of sodium mercaptoethanesulfonate to benzoquinone. The tris‐thioether compound 6 is an analogue of the major byproduct formed during the previously reported synthesis of 4 , [ 22 ] and it was produced by attempting the synthesis of 5 at elevated temperature (see Supporting Information). The yield of the byproduct was instead improved, allowing 6 to be isolated for further studies.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroquinones 1 – 8 were oxidized chemically to the corresponding quinones using a modification of Kochi's previously reported NO x ‐based method (see Supporting Information for details). [ 22,26 ] With the isolated quinones in hand, we examined the stability of the quinone forms of 5 , 6 , and 7 using a 1 H NMR spectroscopic protocol, similar to that previously used with compounds 1 – 4 . [ 22 ] Briefly, samples of each quinone were prepared in 0.5 m D 2 SO 4 with 0.05 m CH 3 SO 3 H as an internal standard, and the fate of each quinone was monitored by 1 H NMR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have reported that quinones act as a redox mediators. [18][19][20][21][22][23][24] Even though the quinoneelectrolyte interface plays an important role as an electron donor/acceptor, there is no consensus about the mechanism of electron transfer. As far as the experimental approach is concerned, there is an intrinsic problem in solving the reaction mechanism: both the mediated electron transfer mechanism and electrocatalysis can result in similar responses in steady-state electrochemistry because both increase the faradaic current at a low overpotential.…”
Section: Nicotinamide Adenine Dinucleotide: Structure and Propertiesmentioning
confidence: 99%
“…3 These results suggest that the electrochemically modified electrode and the FCF electrode treated chemically in phosphate buffer solution (0.1 mol L -1 , pH 7.5) showed the best electrochemical activity towards the NADH electrooxidation. Different mechanisms have been proposed in the literature for the electro-oxidation of NADH in the presence of redox mediator, [18][19][20][21][22][23][24] where the redox mediators have been coupled with NAD-dependent enzymes. In our case, the electro-oxidation of NADH catalyzed by ortho-and anthraquinone modified FCF electrodes is followed by a reaction pathway shown in Figure 22.…”
Section: Electro-oxidation Of Nadh Catalyzed By Quinones On Fcf Surfacementioning
confidence: 99%